Complex response inhibition and cognitive flexibility in school-aged Cypriot-Greek-speaking children who stutter - Paphiti, Maria; Jansson-Verkasalo, Eira; Eggers, Kurt (Frontiers in Psychology, 2022)
Purpose: Over the last few years, research findings have suggested limitations in executive function (EF) of children who stutter (CWS) with the evidence being more consistent in studies with preschoolers (3–6 years old) than in studies with school-aged children (6–12 years old). The purpose of the current study was to assess complex response inhibition and cognitive flexibility in school-aged CWS and their non-stuttering peers. Methods: Participants, 19 CWS (mean age = 7.58 years, range 6.08–9.17) and 19 age- and gender-matched children who do not stutter (CWNS; mean age = 7.58 years, range 6.08–9.33), completed a visual task consisting of three task blocks. Analyses were based on response times and error percentages during the different task blocks. Results: All participants showed expected performance-costs in task block comparisons targeting complex response inhibition and cognitive flexibility. Significant group differences were found in measures of cognitive flexibility with CWS performing slower compared to CWNS (p = .02). Additionally, significant block × group interactions demonstrated that CWS, compared to CWNS, slowed down more (i.e., higher performance-cost) under both complex response inhibition (p = .049) and cognitive flexibility task conditions (p = .04 for no-set-shifting and p = .02 for set-shifting). Conclusions: These results are in line with some of the previous findings in school-aged CWS and suggest that CWS present lower performance in complex response inhibition and cognitive flexibility task conditions when compared to their non stuttering peers.